Ethno Botanical Survey of Gymnema sylvestre in Diabetes Mellitus Patients at Kaithady - Sivarangini, S.; Viviyan, S. (1ST INTERNATIONAL CONFERENCE ON UNANI, AYURVEDA, SIDDHA AND TRADITIONAL MEDICINE - 2013, 2013)
The objective of the study was to investigate the ethno botanical survey of Gymnema sylvestre in diabetes mellitus patients at Kaithady. 80 diabetes patients were identified in the 3 Grama Sevaka (GS) divisions (Kaithady West, South & Southeast) of Kaithady. This study was carried out from March to August 2012. Necessary permission was obtained from the MOH Chavakachcheri and GS of each GS divisions. The identified patients were interviewed through questionnaire and conversation by the researchers for data collection. From the beginning of the study the patient's Fasting Blood Sugar (FBS) sample was collected from their clinic records for 3 months through subsequent visits. This study reveals that most of the patients were from Kaithady Southeast (45%). (57.5%) are men. The age group of 60-69 was (42.5%). (53.75%) had history of diabetes among first degree relatives. The (80%) of the patients had taken G. sylvestre Out of (80%) of the patients (75%) had diet control, Allopathic Medicine & G. sylvestre, (5%) had Allopathic Medicine & G. sylvestre. (80%) of the patients used G. sylvestre as different format. Out of (80%) the patients (40%) were freshly chewing the leaves, (26.25%) had used the leaves as 'varai' or 'sambol', and (13.75%) had used as dry leaves powder. The G. sylvestre using patient's FBS (90.63%) was maintained 126-185mg/dl and (9.38%) had 186-250mg/dl. In G. sylvestre not used (20%) patients their FBS (75%) was maintained 126-185mg/dl and (25%) had 186-250mg/dl. This study concludes that most of the patients had used G. sylvestre to control the diabetes as dietary supplement and as well as the medicine. The usage of G. sylvestre plays an important role in the control of diabetes. Therefore, awareness programs about the usage of G. sylvestre should be conducted to all sections of the society affected by diabetes.
Keywords: Ethno botanical; Gymnema sylvestre; Diabetes mellitus; Kaithady